Efficacy and safety profile of nab-paclitaxel plus gemcitabine in patients with metastatic pancreatic cancer treated to disease progression: a subanalysis from a phase 3 trial (MPACT). Issue 1 (December 2016) - Vogel, Arndt; Römmler-Zehrer, Josefine; Li, Jack; McGovern, Desmond; Romano, Alfredo; Stahl, Michael
Abstract Background The phase 3 MPACT trial in patients with metastatic pancreatic cancer demonstrated superior efficacy ofnab -paclitaxel (nab -P) + gemcitabine (Gem) vs Gem monotherapy for all endpoints examined including overall survival, the primary endpoint. In the MPACT trial, patients were treated until progressive disease (PD) or unacceptable toxicity. The current exploratory analysis investigated outcomes of patients from the MPACT trial who were treated until PD, in order to understand how to maximize treatment benefit fromnab -P + Gem. Methods The trial design has been described in detail previously. Progressive disease was determined by the investigator on the basis of radiological imaging. Results Among patients who were treated until PD, overall survival was significantly longer for those who receivednab -P + Gem vs Gem (median, 9.8 vs 7.5 months;P < 0.001). Independently assessed progression-free survival and overall response rate were significantly greater among patients in the treatment-to-PD cohort who receivednab -P + Gem compared with Gem (P < 0.001 for each). Although not compared statistically, patients who were treated until PD received greater treatment exposure and experienced more favourable efficacy than the intent-to-treat population of the MPACT trial. Among patients who were treated withnab -P + Gem until PD, > 50 % went on to receive a subsequent therapy. The safety profile for patients treated until PD was similar to what was reported in the overall MPACT trial. Conclusion Thenab -P + Gem regimen is an active first-line treatment option; most patients were treated until PD, and this exposure was associated with improved efficacy outcomes. Prolonged first-line treatment exposure and ability to receive subsequent therapies likely contributed to the improved survival among these patients. Our data highlight the importance of managing adverse events and indicate that patients should be treated until PD when possible. Trial registration ClinicalTrials.govNCT00844649 (MPACT trial); Registration date of this prospective phase III trial: February 13, 2009; current exploratory subanalysis was conducted retrospectively.